Regolith Weathering and Sorption Influences Molybdenum, Vanadium, and Chromium Export via Stream Water at Four Granitoid Critical Zone Observatories - Richardson, Justin B.; King, Elizabeth K. (Frontiers in Earth Science, 2018)
Understanding the fate of oxyanions in the Critical Zone is important because of their biological significance and the potential for their use as geochemical tracers in terrestrial environments and subsurface systems. This study assessed the partitioning and transport of a suite of oxyanion metals (Mo, V, and Cr) in regolith profiles and stream waters from four granitoid Critical Zone Observatories (CZOs) (Boulder Creek, Calhoun, Luquillo, and Southern Sierra). For regolith profiles, we compared Mo, V, and Cr in total digestions and two extractions targeting oxyanions adsorbed to organic matter and amorphous oxides (H2O2 + 0.1 M acetic acid) and secondary Fe oxides (citrate–bicarbonate–dithionite). Total Mo, V, and Cr ranged from 0.4 to 2.5 mg kg-1, 16 to 208 mg kg-1, and 0.2 to 55 mg kg-1, respectively. The greatest concentrations of the oxyanions did not occur in surface soil samples, nor deepest regolith samples (7–10 m in depth), but instead in subsurface peaks that corresponded with secondary Fe oxides and total organic carbon. The average organic and amorphous oxide bound phase was 0.1–3.5% while the secondary Fe oxide fraction was 4–27% of the respective total concentrations for oxyanions, suggesting that secondary Fe oxides were an important phase across the regolith profile. Stream water Mo, V, and Cr concentrations ranged from 0.02 to 0.25 μg L-1, 0.2 to 1.8 μg L-1, and 0.08 to 0.44 μg L-1, respectively. Our results demonstrate that the deep regolith (2–7 m in depth) play an active role in both sourcing and retention of oxyanions. In addition, we observed that increased weathering intensity at warmer, wetter climates does not always lead to increased depletion in regolith or stream water export, which implies the importance of transport processes within regolith. Further quantification of oxyanion export from regolith can aid in developing their use as geochemical tools for global weathering.